Urban Exile : Collected Writings Of Harry Gamboa Jr. - Jr., Harry Gamboa (Book collections on Project MUSE., 1998)
Harry Gamboa Jr. has pioneered multimedia formats for nearly three decades, setting a precedent for the work of artists such as Coco Fusco, Guillermo Gmez-Pea, and Daniel J. Martinez. Urban Exile gathers Gamboas diverse creations in a visually compelling collection that reveals a rich vein of Chicano avant-garde production reaching back to the early 1970s.